Framing Financial Markets: A Methodological Account - Dow, Sheila (Brazilian Keynesian Review, 2017)
The way in which financial markets are framed depends on who is doing the framing, although there are reflexive interdependencies between these framings. The underlying argument of the paper is that the way in which financial markets are framed in theory should reflect the different framings in the economy, and that this may benefit from input from other disciplines. Mainstream economics frames financial markets as archetypical competitive markets, focusing on prices as the key information on which to base analysis. This follows from traditional positivist methodology where computability is the key to theory appraisal. Central banks draw on this analysis for their own framing, but modify it significantly in the face of the requirement to take decisions under palpable uncertainty; some understanding is perceived to be necessary for prediction. Increasingly their role is seen as manipulating expectations in order to achieve inflation targets. Participants in financial markets in turn employ quantitative models for forming their expectations; in conditions of market turbulence the limits to these models become evident, and indeed material to prices themselves. Further, for these participants, markets are a social phenomenon. Finally the households whose experience of financial markets enables or constrains spending frame financial markets in yet another way. Understanding of these various framings would benefit from recourse to other disciplines, notably psychology, sociology and rhetoric. But methodological approach is critical for how these inputs can enhance theorising, as exemplified by the difference between the old and new behavioural economics.